APPARATUS FOR MAINTAINING GAS PRESSURE DURING A GAS EXCHANGE PROCESS - John Dingley (2005)
Inventor:DINGLEY JOHN [GB]Applicant:ART OF XEN LTD [GB]CPC:IPC:A61MPublication info:YU41503 (A)2005-06-10Priority date:2000-11-28